Impact of Two Different Antimicrobial Stewardship Methods on Frequency of Streamlining Antimicrobial Agents in Patients with Bacteremia. (9th November 2016) - Lukaszewicz Bushen, Jennifer; Mehta, Jimish M.; Hamilton, Keith W.; Shawn Binkley,; Timko, Daniel R.; Lautenbach, Ebbing; Pegues, David A.
Abstract : OBJECTIVE: To assess the likelihood of antimicrobial streamlining between 2 antimicrobial stewardship methods. DESIGN: Retrospective cohort study. SETTING: Large academic medical center. METHODS: Frequency and time to antimicrobial streamlining were compared during a prior authorization and a prospective audit period. Streamlining was defined as an antimicrobial change to a narrower agent if available or to a broader agent if the isolate was resistant to empiric therapy. Patients included were ≥18 years old with monomicrobial bacteremia with S. aureus, Enterococcus spp., or any aerobic Gram-negative organism. RESULTS: A total of 665 cases of bacteremia met inclusion criteria. Frequency of streamlining was similar between periods for all cases of bacteremia (audit vs restriction: 60.7% vs 53.2%; P =.12), S. aureus bacteremia (73.2% vs 76.9%; P =.671), and Enterococcus bacteremia (81.6% vs 71.9%; P =.335). Compared to restriction, the audit period was associated with an increased frequency of streamlining for cases of Gram-negative bacteremia (51.4% vs 35.6%; odds ratio [OR], 1.85; 95% confidence interval [CI], 1.06–3.25), those on the medical service (67.9% vs 53.1%; OR, 1.86; 95% CI, 1.09–3.16), and those admitted through the emergency department (71.6% vs 51.4%; OR, 2.32; 95% CI, 1.24–4.34). Characteristics associated with increased streamlining included: absence of β-lactam allergy ( P <.001), Gram-negative bacteremia ( P <.001), admission through the emergency department ( P =.001), and admission to a medical service ( P =.011). CONCLUSIONS: Compared with prior authorization, prospective audit increased antimicrobial streamlining for cases of Gram-negative bacteremia, those admitted through the emergency department, and those admitted to a medical but not surgical service. Infect Control Hosp Epidemiol 2016:1–7